PENGARUH MEDIA DAUN TERHADAP HASIL BELAJAR TEMATIK BAGI PESERTA DIDIK KELAS IV SEKOLAH DASAR - lisnani, lisnani (Program Studi Pendidikan Guru Sekolah Dasar Universitas Katolik Musi Charitas, 2019)
The use of thematic learning models uses a scientific approach in line with the enactment of the 2013 curriculum. Where several subjects are combined into one theme known as thematic learning. In the 2013 curriculum there is a thematic learning precisely on theme 3 on Caring for Living Things in Mathematics, Natural Sciences, and Cultural Arts and Crafts (SBdP). The purpose of this study was to determine how the influence of the use of leaf media on the thematic learning outcomes of fourth grade students. This type of research is quantitative research. Categorized as quantitative research because it is classified as experimental research that measures student learning outcomes. Subjects in this study were grade 4 students at SD Negeri 42 with 2 classes, namely IV A and IV B, each of which had 25 students. Data collection techniques in the form of tests, interviews, and documentation. Homogeneity test data analysis techniques, normality test, and independent sample t-test using SPSS 17. The results of this study in the form of the influence of leaf media on the thematic learning outcomes of fourth grade elementary school students can be seen from the value of sig (2-tailed) = 0,000 <0.05 which means that H0 is rejected and Ha is accepted and the average value of thematic learning outcomes of students who use leaf media is higher than the average value of students who do not use leaf media.